2013
DOI: 10.1186/1757-4749-5-27
|View full text |Cite
|
Sign up to set email alerts
|

Timely approaches to identify probiotic species of the genus Lactobacillus

Abstract: Over the past decades the use of probiotics in food has increased largely due to the manufacturer’s interest in placing “healthy” food on the market based on the consumer’s ambitions to live healthy. Due to this trend, health benefits of products containing probiotic strains such as lactobacilli are promoted and probiotic strains have been established in many different products with their numbers increasing steadily. Probiotics are used as starter cultures in dairy products such as cheese or yoghurts and in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 117 publications
(197 reference statements)
2
59
0
1
Order By: Relevance
“…Probiotic products need to contain at least 10 6 colony-forming units (CFU) per gram for the duration of the product's shelf life in order to transfer beneficial effects to the host [10]. Acid production by probiotic culture, oxygen permeability through the package, and physical condition of product storage can decrease the viability and sensory characteristics of a probiotic product before the end of its shelf life [11,12]. In this study, L. rhamnosus GR-1 was the technological starter culture used to ferment the rice pudding samples.…”
Section: Introductionmentioning
confidence: 99%
“…Probiotic products need to contain at least 10 6 colony-forming units (CFU) per gram for the duration of the product's shelf life in order to transfer beneficial effects to the host [10]. Acid production by probiotic culture, oxygen permeability through the package, and physical condition of product storage can decrease the viability and sensory characteristics of a probiotic product before the end of its shelf life [11,12]. In this study, L. rhamnosus GR-1 was the technological starter culture used to ferment the rice pudding samples.…”
Section: Introductionmentioning
confidence: 99%
“…Use of Lactobacillus to control canine intestinal infections is an interesting proposal [13]. Lactobacillus is an economically important organism, especially as bioactive molecules, probiotic, preservative, fermentation and maturation of the sausages, milk products [14][15][16][17][18]. The dominance of Lactobacillus species such as L. iners, L. jensenii, L. gasseri, and L. crispatus in the vaginal region acts as a barrier for invasion of pathogenic bacteria and virus.…”
Section: The Trouble With Lactobacillus Identificationmentioning
confidence: 99%
“…Comparison of information deduced from sequenced genomes of Lactobacillus ruminis ATCC 27782 (2.06 Mb) isolated from bovine and L. ruminis strain, ATCC 25644 (2.138 Mb), isolated from human with L. salivarius core proteins showed that Lactobacillus species are categorized into 4 phylogenetically distinguishable groups [42]. Proteomics studies have proved helpful in identifying 6 proteins which can be used as biomarkers for selecting their probiotic potential since they are responsible for responding to bile salt and adaptation in L. plantarum [16]. Information on how Lactobacillus casei might have undergone diversity to adapt to the environment has been elucidated through completely sequencing its genome [39].…”
Section: The Trouble With Lactobacillus Identificationmentioning
confidence: 99%
“…It can also be isolated from beverages and foods such as wine, milk, kefir, meat, fruit, vegetables, cereals and dairy products, mainly in yogurts and cheeses (Pál et al, 2012;Herbel et al, 2013;Barrangou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The genus Lactobacillus is characterized by the low G + C content (guanine and cytosine -33 to 52%) in the genome. They are carbohydrate fermenting microorganisms, and lactic acid is the major final product of this metabolism (Cai et al, 2012;Herbel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%